ANALISA CTDI PADA PERMUKAAN DAN PUSAT PHANTOM MENGGUNAKAN CT DOSE PROFILER - Cory Amelia; Evi Setiawati; Zaenal Arifin (Youngster Physics Journal, 2014)
The research has been done on the comparative value of CTDI on the surface and the center of the phantom. This research was conducted to determine the value of CTDI on the top surface, center, and bottom of the phantom using the CT Dose Profiler on CT scan head and determine the effect of tube voltage on the value of CTDI. The research was conducted with take a CTDI data using the CT Dose Profiler on spiral CT scan mode and using a phantom head. Measurements a CTDI conducted on the top surface, center and bottom surface of the phantom with the variation of the tube voltage value is 80 kV, 100 kV, and 120 kV, and current value 320 mA, time 18.5 s, pitch 0,531, slice thickness 5 mm, and scan length 180 mm. The results of measurements the value of CTDI with variation a tube voltage on the top surface of the phantom was 22.75 mGy to 62.97 mGy, the center of phantom was 19.34 mGy to 59.66 mGy and the bottom surface of the phantom was 20.10 mGy to 54, 19 mGy.  Keywords: Head Phantom, the CT Dose Profiler, CTDI, Tube Voltage.